Acute Fatty Liver of Pregnancy: A Review of Maternal Morbidity in 13 Patients Seen Over 12 Years in Nova Scotia - Connie D Hoare; Dickran A Malatjalian; Bernard W Badley; Joseph J Sidorov; C Noel Williams (Canadian Journal of Gastroenterology)
OBJECTIVE: To review the maternal and fetal survival in all cases of acute fatty liver of pregnancy seen by the Division of Gastroenterology at Grace Maternity Hospital and the Victoria General Hospital from 1979-91.